Using a high density bin map to analyze quantitative trait locis of germination ability of maize at low temperatures - Zhou, Yu; Lu, Qing; Ma, Jinxin; Wang, Dandan; Li, Xin; Di, Hong; Zhang, Lin; Hu, Xinge; Dong, Ling; Liu, Xianjun; Zeng, Xing; Zhou, Zhiqiang; et al. (Frontiers in Plant Science, 2022)
Low temperatures in the spring often lead to a decline in the emergence rate and uniformity of maize, which can affect yield in northern regions. This study used 365 recombinant inbred lines (RILs), which arose from crossing Qi319 and Ye478, to identify low-temperature resistance during the germination stage by measuring eight low-temperature-related traits. The QTLs were mapped using R/qtl software by combining phenotypic data, and we used the genotyping by sequencing (GBS) method to produce a high-density genetic linkage map. Twenty QTLs were detected during QTL mapping, of which seven QTLs simultaneously detected a consistent 197.10-202.30Mb segment on chromosome 1. The primary segment was named cQTL1-2, with a phenotypic variation of 5.18%-25.96% and a physical distance of 5.2Mb. This combines the phenotype and genotype with the identification of seven chromosome segment substitution lines (CSSLs), which were derived from Ye478*Qi319 and related to cQTL1-2. The physical distance of cQTL1-2 was reduced to approximately 1.9Mb. The consistent meta-QTL mQTL1 was located at 619.06cM on chromosome 1, had a genetic distance of 7.27cM, and overlapped with cQTL1-2. This was identified by combining the results of previous QTL studies assessing maize tolerance to low temperatures at the germination stage. An assessment of the results of the RIL population, CSSLs, and mQTL1 found the consistent QTL to be LtQTL1-1. It was identified in bin1.06-1.07 at a confidence interval of between 200,400,148 and 201,775,619bp. In this interval, qRT-PCR found that relative expression of the candidate genes GRMZM2G082630 and GRMZM2G115730 were both up-regulated in low-temperature tolerant lines and down-regulated in sensitive lines (P<0.01).